Case Report: Multidisciplinary management of primary omental pregnancy involving intraoperative ultrasound - Wang, Shanshan; Shao, Huaguo; Huang, Yan; Li, Yanqing; Feng, Ting; Pan, Lin (Frontiers in Medicine, 2025)
IntroductionPrimary omental pregnancy (OP) is very rare, and achieving an accurate diagnosis has always been a challenge for obstetricians, gynecologists, and sonographers. Our attempt to utilize intraoperative ultrasonography has facilitated a definitive diagnosis for masses lacking obvious purple or blue characteristics under observation. This approach could provide a solution for challenges faced in intraoperative diagnosis.Case presentationWe present the case of an 18-year-old woman who was 5 months postpartum and presented with intermittent lower abdominal pain for 3 days with no obvious causes. Emergency ultrasonography diagnosed an abdominal pregnancy (AP) with abdominal and pelvic hemorrhage. Laparoscopic surgery revealed a mass on the omentum, but the surface lacked the typical purple-blue appearance. Intraoperative ultrasonography was employed, and the suspicious omental mass was shifted to the left pelvic wall. Under ultrasound guidance, the echo of a gestational sac (GS) was observed within the mass. The AP tissue and a portion of the omentum were resected. Examination of the resected omental specimen revealed chorionic villi tissue. The diagnosis was confirmed as primary OP. The operations were successful, and the patient recovered well postoperatively.ConclusionDue to early detection, the patient received timely treatment, which played a crucial role in selecting the therapeutic plan. Chronic pelvic inflammatory disease (PID) was identified intraoperatively, suggesting that it may be a potential risk factor for OP. It is imperative for us to gain a deeper understanding of the diagnosis of primary OP, analyze its potential precipitating factors, and expand the scope of ultrasonographic examination by searching for a GS in other locations when none is visualized within the uterine cavity.